Child Abuse and the Psychological Dispositions of Pain Catastrophising, Resilience and Hope. (1st October 2021) - Zlotnick, Cheryl; Grouper, Hadas; Pud, Dorit
Abstract : Associations between psychological dispositions and adverse childhood experiences (ACEs) tends to vary by ACE category (i.e. childhood abuse, childhood neglect, family dysfunction), particularly for adults with high ACE scores (>4 on a 0–10 scale). Psychological dispositions (such as pain catastrophising, hope, resilience), however, have typically been examined as intermediary factors rather than endpoints (i.e. dependent variables) on mostly adult patients. In this cross‐sectional study on healthy adults who completed self‐report questionnaires, we hypothesised that even with low ACEs scores (≤4 ACEs), adults with childhood abuse (compared to childhood neglect and family dysfunction, and no ACEs) will have higher pain catastrophising and lower resilience and hope. In healthy adults ( n  = 47), multivariate analysis of covariance (MANCOVA) indicated that ACE categories and gender were associated with the three dispositions (Pillai's F(6, 84)  = 2.518, p  = 0.027, η 2  = 0.152). Univariate results revealed an association between childhood abuse versus no ACEs and pain catastrophising (Pillai's F(2, 43)  = 7.084, p  = 0.002, η 2  = 0.248). No associations were found between the ACEs categories and hope or resilience. Among healthy adults with few ACEs, history of childhood abuse was uniquely associated with pain catastrophising. Although a sensitive topic, assessing history of childhood abuse would enable health professionals to provide proactive interventions reducing harmful reactions to pain, such as pain catastrophising. 'We hypothesised that even with low ACEs scores… adults with childhood abuse… will have higher pain catastrophising and lower resilience and hope' Key Practitioner Messages: History of childhood abuse in healthy adults has a uniquely important association with pain catastrophising. Gender did not influence the link between history of childhood abuse and pain catastrophising in healthy adults. In this study, history of adverse childhood experiences was not associated with hope and resilience in healthy adults.